Wheat Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2002)
This publication projects a budget that reflects expected income and costs based on wheat production in south central Kansas.
MF574_2002_10
Keywords: MF574; Economics; Crops; MF